2018
DOI: 10.26442/terarkh201890665-73
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the results of analgesic therapy. Results of the Russian multicentre study of NOTE (NSAID: Open-label Trial of Efficacy)

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are most popular medications for the treatment of pain in common musculoskeletal diseases such as osteoarthritis (OA) and non-specific low back pain (LBP). However, the factors affecting the effectiveness of these drugs have not been determined fully. Aim: to identify factors affecting the effectiveness of NSAIDs in patients with OA and LBP. Materials and methods. An observational study was conducted to evaluate the effectiveness of a 2-week course of NSAIDs in OA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Hancock et al [18] found that female patients and patients having high levels of physical activity-related fear avoidance may respond better to NSAIDs as compared to males and those with low levels of physical activity related fear avoidance. In 2018, an observational study on patients with osteoarthritis and non-specific LBP [19] reported that the effect of NSAIDs was smaller in patients aged 65 years and older, with body mass index >30 kg/m2, experiencing severe pain, pain at rest, pain at night, and the presence of spinal stiffness. Given the potential variation in the effectiveness of NSAIDs in patients with LBP, we hypothesize the presence of distinct 'subgroups' among those with acute and sub-acute LBP, exhibiting differential responses to NSAIDs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hancock et al [18] found that female patients and patients having high levels of physical activity-related fear avoidance may respond better to NSAIDs as compared to males and those with low levels of physical activity related fear avoidance. In 2018, an observational study on patients with osteoarthritis and non-specific LBP [19] reported that the effect of NSAIDs was smaller in patients aged 65 years and older, with body mass index >30 kg/m2, experiencing severe pain, pain at rest, pain at night, and the presence of spinal stiffness. Given the potential variation in the effectiveness of NSAIDs in patients with LBP, we hypothesize the presence of distinct 'subgroups' among those with acute and sub-acute LBP, exhibiting differential responses to NSAIDs.…”
Section: Methodsmentioning
confidence: 99%
“…Our objectives are: (1) to assess the overall treatment effect of NSAID for improving pain, disability, and health-related quality of life in adults with acute and subacute LBP; (2) to identify the potential moderation of baseline patients’ characteristics on treatment effects. Based on the precious studies [ 18 , 19 ], we hypothesize that the following subgroups: patients who are female; having high levels of physical activity-related fear avoidance; aged under 65 years; body mass index ≤ 30 kg/m2; experiencing slighter pain; without pain at rest; without pain at night; without spinal stiffness, may demonstrate a more favorable response to NSAIDs. Our primary outcomes of interest are pain intensity, disability, and health-related quality of life, secondary outcomes are adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…По результатам российского многоцентрового исследования НОТА также показано, что НПВП как класс являются средством выбора для лечения боли при неспецифической боли в спине и остеоартрите, а ацеклофенак, в частности, эффективен и безопасен при данной патологии [35].…”
Section: îáñóAeäåíèåunclassified
“…Currently, the pharmaceutical industry offers a practitioner more than 70 NSAIDs of various chemical structures (Lesnaya 2018). However, the main stumbling block in the treatment of patients with pain syndrome is their very low safety profile (Fanella et al 2017;Karateev et al 2018;Lesnaya 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, unfortunately, along with high pharmacotherapeutic efficacy for the main indications, it is the use of NSAIDs that a whole spectrum of complications is associated with (ulcerogenicity, hepatotoxicity, hematotoxicity, neurotoxicity, cardiotoxicity, etc.) (Nozadze et al 2016;Parada et al 2016;Karateev et al 2018).…”
Section: Introductionmentioning
confidence: 99%